Advanced glycation end products in human diabetic lens capsules. (September 2021) - Rankenberg, Johanna; Rakete, Stefan; Wagner, Brandie D.; Patnaik, Jennifer L.; Henning, Christian; Lynch, Anne; Glomb, Marcus A.; Nagaraj, Ram H.
Abstract: Advanced glycation end products (AGEs) accumulate with age in human lens capsules. AGEs in lens capsules potentiate the transforming growth factor beta-2-mediated mesenchymal transition of lens epithelial cells, which suggests that they play a role in posterior capsule opacification after cataract surgery. We measured AGEs by liquid chromatography-mass spectrometry in capsulorhexis specimens obtained during cataract surgery from nondiabetic and diabetic patients with and without established retinopathy. Our data showed that the levels of most AGEs (12 out of 13 measured) were unaltered in diabetic patients and diabetic patients with retinopathy compared to nondiabetic patients. There was one exception: glucosepane, which was significantly higher in diabetic patients, both with (6.85 pmol/μmol OH-proline) and without retinopathy (8.32 pmol/μmol OH-proline), than in nondiabetic patients (4.01 pmol/μmol OH-proline). Our study provides an explanation for the similar incidence of posterior capsule opacification between nondiabetic and diabetic cataract patients observed in several studies. Highlights: Advanced glycation endproducts (AGEs) in human lens capsules were measured by LC-MS/MS. The levels of majority of AGEs were similar between diabetic and nondiabetic lens capsules. Glucosepane levels were significantly higher in diabetic than in nondiabetic lens capsules.